1997
DOI: 10.2490/jjrm1963.34.40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Balneotherapy on Atopic Dermatitis at Kusatsu.

Abstract: From June 1990 to May 1995, 46 patients with atopic dermatitis (31 males and 15 females, 2511 years) were admitted to our hospital to receive balneotherapy using Kusatsu hot-spring water. The atopic dermatitis in all but 4 cases occurred while the patients were still under 20 and had been refractory to various treatments including steroid ointment therapy over a long period of time. A week's observation allowing only a hot fresh water shower to remove environmental factors, resulting in no change in their skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The most significant effect was decrease in blood pressure during bathing for 2*20 min, both systolic and diastolic blood pressure dropped for around 10 mmHg. Kubota [ 23 ] and Ekmekcioglu et al [ 3 ] show short term effect of hot spring bathing on decrease of blood pressure (Kubota et al, −11 mmHg after bathing in 42 °C for 10 min [ 23 ]), which reflected the physical effect when human soaked into higher temperature of bathing water than body temperature. Ono et al reports that during bathing, the decrease in SBP observed 4 min after the start of the bathing (−26 ± 7 mmHg at 39 °C for the older men, and −8 ± 9 mmHg at 39 °C for the younger men) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant effect was decrease in blood pressure during bathing for 2*20 min, both systolic and diastolic blood pressure dropped for around 10 mmHg. Kubota [ 23 ] and Ekmekcioglu et al [ 3 ] show short term effect of hot spring bathing on decrease of blood pressure (Kubota et al, −11 mmHg after bathing in 42 °C for 10 min [ 23 ]), which reflected the physical effect when human soaked into higher temperature of bathing water than body temperature. Ono et al reports that during bathing, the decrease in SBP observed 4 min after the start of the bathing (−26 ± 7 mmHg at 39 °C for the older men, and −8 ± 9 mmHg at 39 °C for the younger men) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the aspect of cardiac function, heart rate may be increased up to 20%, and was still above baseline even after 2*20 min bathing and rested for 2*20 min (+1.44 b.p.m., p < 0.05). Kubota et al demonstrate that the heart rate went back to baseline after 10-min bathing in 42 °C and rested for around 10 min [ 23 ]. ŞAŞ et al presents that the patients with musculoskeletal disease who received 36 °C to 40 °C bathing for 10 days (5 times/week, 20 min/day), the significant increase of heart rate persisted in both 1st and 10th sessions of balneotherapy even after 10 min resting [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for the skin, it has been reported that various therapeutic effects can be expected by hot spring bathing. For example, acidic hot springs are famous for their ability to improve the symptoms of atopic dermatitis [ 27 , 36 , 37 , 38 , 80 ], and the sulfur spring and Dead Sea spa regulate melanin production [ 13 , 58 , 61 ]. Furthermore, the effectiveness of hot-spring bathing for various diseases such as psoriasis and ichthyosis has been reported [ 16 , 24 , 35 , 36 , 37 , 41 , 42 , 45 ].…”
mentioning
confidence: 99%
“…For example, acidic hot springs are famous for their ability to improve the symptoms of atopic dermatitis [ 27 , 36 , 37 , 38 , 80 ], and the sulfur spring and Dead Sea spa regulate melanin production [ 13 , 58 , 61 ]. Furthermore, the effectiveness of hot-spring bathing for various diseases such as psoriasis and ichthyosis has been reported [ 16 , 24 , 35 , 36 , 37 , 41 , 42 , 45 ]. Alkaline hot springs are supposed to stimulate the skin less than acid hot springs and help smooth the skin; however, this has not been clearly elucidated.…”
mentioning
confidence: 99%